PWM Regulation of Grid-Tied PV System on the Base of Photovoltaic-Fed Diode-Clamped Inverters - Oleschuk V.I.; Ermuratskii V.V. (Problems of the Regional Energetics)
Investigation of grid-tied photovoltaic system on the base of two diode-clamped inverters, controlled by specific algorithms of pulse-width modulation (PWM), has been done. This system includes two strings of photovoltaic panels feeding two diode-clamped inverters. The outputs of inverters are connected with the corresponding windings on the primary side of three-phase transformer, connected with a grid. In order to reduce phase voltage distortion and to increase efficiency of operation of the system, special scheme of control and modulation of inverters has been used, providing minimization of common-mode voltages and voltage waveforms symmetries under different operating conditions. Detailed simulation of processes in this photovoltaic-fed power conversion system has been executed. The results of simulations verify good performance of photovoltaic system regulated in accordance with specific strategy of control and modulation.